"Exploring Aesthetic Practices Conference". Сonference review, University of Jyväskylä, Finland, 23–25.10.2025 - Butsykina, Yevheniia (Ukrainian Cultural Studies, 2024)
Overview of the conference "Exploring Aesthetic Practices", which took place from October 23 to 25, 2024 at the Department of Art Education, Faculty of Humanities and Social Sciences, Jyväskylä University of Applied Sciences.